The first case of pediatric bile duct adenoma - Zhi Li; Xiaoyi Sun; Jiexiong Feng (Elsevier, 2015)
Intrahepatic bile duct adenoma (BDA) is a rare benign epithelial liver tumor derived from bile duct cells. We report the first case of pediatric bile duct adenoma in the world. Furthermore, we review the diagnosis, pathology, treatment and prognosis of bile duct adenoma.